Human Resource Function Effectiveness Assessment Through Management Audit (Case Study in UB Hotel) - Akrom, Ihwanda; Widijoko, Grace (Jurnal Ilmiah Mahasiswa FEB, 2014)
Research on management audit in human resource function is aimed to comprehend the achievement of effectiveness in human resource function that has been conducted by UB Hotel and to figure out the occurring drawbacks that cause the ineffectiveness. This research discusses human resource function which is accomplished through qualitative descriptive applied research method. The data are collected from field study through interview, questionnaire, documentation, and observation. Data analysis involves four (4) important elements for management audit, including: criteria, condition, cause and effect. The process can reveal the level of effectiveness of human resource function in managing human resource at UB Hotel. The audit scope discussed in this research involves ten (10) functions, namely: human resource planning, recruitment, selection, orientation and positioning, training and development, performance assessment, planning and development of career, compensation, worker protection, and work termination. Based on the result that is derived from a comprehensive analysis it concludes that human resource function in UB Hotel has been managed effectively in accordance with the applicable policy and regulation; however, there is one function which is not effective yet namely the selection of human resource function. Based on the findings of this research, there are some recommendations and suggestions to achieve greater improvement in the development and management of human resource in the future which are, the online recruitment process that use UB Hotel website, the need to implement medical test in the selection stages, and the requirement and the openness from management in career promotion.Key words : UB Hotel, management audit, human resource function, effectiveness, criteria, condition, cause, effect, recommendation